Clinical characteristics of ultra-longitudinally extensive transverse myelitis in a Peruvian cohort - E. Guevara-Silva; C. Caparó-Zamalloa; V. Osorio-Marcatinco; K. Álvarez-Toledo; S. Castro-Suarez (Neurology Perspectives, 2024)
Introduction: Ultra-longitudinally extensive transverse myelitis (uLETM) is defined as an inflammatory lesion involving 10 or more spinal cord segments. The aim of our study is to describe the clinical and radiological features of this atypical form of myelitis. Methods: We conducted a descriptive cross-sectional study of clinical data from 57 patients older than 18 years diagnosed with longitudinally extensive transverse myelitis. Nineteen cases were classified as uLETM. Results: Twelve of the 19 patients were women, age ranged between 18 and 76 years, and the main aetiology was neuromyelitis optica spectrum disorder (8 patients), followed by anti-MOG antibody myelitis (3 patients). The main region involved was at cervical-thoracic spinal cord. Two patients presented complete spinal cord lesion. Conclusions: Our results are consistent with previous reports suggesting that neuromyelitis optica spectrum disorder remains the main aetiology in uLETM; however, anti-MOG antibodies should be considered within the differential diagnosis. Resumen: Introducción: La mielitis longitudinal ultra extensa se define como el compromiso inflamatorio de 10 o más segmentos medulares. El objetivo de nuestro estudio es describir las características clínicas y radiológicas de esta forma atípica de mielitis. Métodos: Realizamos un estudio transversal y descriptivo en base a los datos clínicos de 57 pacientes mayores de 18 años con diagnóstico de mielitis longitudinal extensa. Diecinueve pacientes cumplían con la definición de mielitis longitudinal ultra extensa. Resultados: Doce de los 19 pacientes fueron del sexo femenino, el rango de edad estuvo entre los 18 y 76 años, la principal etiología fue el trastorno del espectro de la neuromielitis óptica (8 pacientes), seguido de la mielitis por anticuerpos anti-MOG (3 pacientes). La principal región comprometida fue a nivel cervicodorsal. Dos pacientes sufrieron una lesión completa de la médula espinal. Conclusiones: Nuestros resultados concuerdan con lo publicado en que el espectro de la neuromielitis óptica sigue siendo la principal etiología en la mielitis longitudinal ultra extensa; sin embargo, el anticuerpo anti MOG debe considerarse dentro del diagnóstico diferencial.